APAKAH PELAPORAN BERKELANJUTAN MEMODERASI RELEVANSI NILAI INFORMASI AKUNTANSI? - Randy Kuswanto (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2019)
This study aims to obtain empirical evidence about the effect of sustainability reporting as a moderating variable on value relevance concept. Prior studies suggest that sustainability report can enhance the company’s financial performance which has similar context with value relevance. This study modifies Ohlson Model (1995) with additional moderating variable to capture the effect of sustainability reporting in Indonesia. The population in this study is all public listed company in Indonesia Stock Exchange in 2016. Pair matching and purposive sampling is used as a sampling method to collect 76 samples. The results of this study show sustainability reporting failed to indicate its moderating effect both on the interaction with earning and book value. Nevertheless, value relevance of group who published the sustainability report is higher than the opposite group. As a final result, this study provides empirical evidence that sustainability report cannot increase the firm value in value relevance model but could increase the level of value relevance itself.